2010
DOI: 10.1007/s10327-010-0241-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the triple gene block sequence in an important melon pathogen, Melon yellowing-associated virus

Abstract: A novel viral disease of melon, caused by Melon yellowing-associated virus (MYaV), has become one of the most serious problems for melon production in Brazil. Despite its importance, little is known about the genome sequence of the virus. In this study, the triple gene block genomic region including the 3 0 -end region of an isolate of MYaV was elucidated (ca. 3.1 kb). Sweet potato chlorotic fleck virus, a newly suggested carlavirus species, was the most closely related virus with 62% nucleotide identity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…"Melon yellowing" is the primary viral disease of melon plants in Brazil [10,25]. This disease is often found in mixed infections with at least three viruses infecting melon plants, such as CABYV, transmitted by aphids, and CWBWV, which, like MYAV, is transmitted by the whitefly B. tabaci MEAM1 species [10,183]. Symptoms caused by virus infection on plants mainly develop on older leaves with yellowing and mottling, as well as the reduction of solid soluble content ( • Brix) in the fruits [10].…”
Section: Whitefly-borne Viruses In Cucurbitaceousmentioning
confidence: 99%
“…"Melon yellowing" is the primary viral disease of melon plants in Brazil [10,25]. This disease is often found in mixed infections with at least three viruses infecting melon plants, such as CABYV, transmitted by aphids, and CWBWV, which, like MYAV, is transmitted by the whitefly B. tabaci MEAM1 species [10,183]. Symptoms caused by virus infection on plants mainly develop on older leaves with yellowing and mottling, as well as the reduction of solid soluble content ( • Brix) in the fruits [10].…”
Section: Whitefly-borne Viruses In Cucurbitaceousmentioning
confidence: 99%
“…The aa sequences of the TGBs of the MYaV-M22 isolate (this study) and the homologous sequences of a previously reported isolate (Nagata et al, 2010) differed, with 90.6% aa sequence identity for TGB1, 94.5% for TGB2, and 92.5% for TGB3. The CP aa sequence of these isolates shares 97.5 % identity; and that of NaBp, 94.8% identity.…”
Section: Discussionmentioning
confidence: 48%